Benefit–risk profile of tofacitinib in patients with moderate‐to‐severe chronic plaque psoriasis: pooled analysis across six clinical trials3. (10th October 2018) - Strober, B.E.; Gottlieb, A.B.; van de Kerkhof, P.C.M.; Puig, L.; Bachelez, H.; Chouela, E.; Imafuku, S.; Thaçi, D.; Tan, H.; Valdez, H.; Gupta, P.; Kaur, M.; et al.
Summary: Background: Although existing psoriasis treatments are effective and well tolerated in many patients, there is still a need for new effective targeted treatment options. Tofacitinib is an oral Janus kinase inhibitor that has been investigated in patients with moderate‐to‐severe chronic plaque psoriasis. Objectives: To consider the benefits and risks of tofacitinib in patients with moderate‐to‐severe psoriasis. Methods: Data were pooled from one phase II, four phase III and one long‐term extension study comprising 5204 patient‐years of tofacitinib treatment. Efficacy end points included patients achieving Physician's Global Assessments of 'clear' or 'almost clear', ≥ 75% and ≥ 90% reduction in Psoriasis Area and Severity Index (coprimary end points) and improvements in Dermatology Life Quality Index score, Hospital Anxiety and Depression Scale depression score and Itch Severity Item score, at weeks 16 and 52. Safety data were summarized for 3 years of tofacitinib exposure. Results: Tofacitinib 5 and 10 mg twice daily (BID) showed superiority over placebo for all efficacy end points at week 16, with response maintained for 52 weeks of continued treatment. Tofacitinib improved patients' quality of life and was well tolerated. Rates of safety events of interest (except herpes zoster) were similar to those in the published literature and healthcare databases for other systemic psoriasis therapies. Tofacitinib 10 mg BID demonstrated greater efficacy than 5 mg BID. Conclusions: Tofacitinib has a benefit–risk profile in moderate‐to‐severe psoriasis consistent with that of other systemic treatments. Abstract : What's already known about this topic? Psoriasis is a chronic, systemic inflammatory disease, which has a significant impact on patients' health‐related quality of life. Although several existing psoriasis treatments are efficacious and well tolerated in many patients, some patients require treatment switching, and a proportion of patients remain untreated or undertreated. Potential challenges to the use of existing therapies include safety issues and limited efficacy in some patients with conventional oral psoriasis treatments, inconvenience of topical treatments and the requirement for parenteral administration of biologics. What does this study add? Consistent efficacy and a safety profile consistent with that seen in rheumatoid arthritis, psoriatic arthritis and ulcerative colitis were demonstrated for oral tofacitinib in patients with moderate‐to‐severe psoriasis. Tofacitinib has a benefit–risk profile in patients with moderate‐to‐severe psoriasis that is consistent with that of other systemic psoriasis treatments. Linked Comment: Fleming. Br J Dermatol 2019;180 :13–14 . Plain language summary available online Respond to this article